2019
DOI: 10.1080/1540496x.2019.1575724
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers in Sub-Saharan Africa’s Sovereign Eurobond Yields

Abstract: This study investigates the possibility of spillovers among Sub-Saharan African (SSA) eurobonds from January 2015 to June 2017 using secondary market yields. Ours results indicate significant contagion effects among these bonds, effects that prove sensitive to major economic events and news announcements. They also suggest that less resilient economies transmit more to and receive less spillovers from their peers. SSA eurobond issuers can therefore increase their influence over the performance of their securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Emenike (2018) further demonstrated that the existence of bidirectional shock and volatility spillover between the Nigerian naira and CFA franc indicates an element of financial integration in West Africa. Senga and Cassimon (2019) documented, amongst others, the existence of significant integration among sub‐Saharan African bonds, and that less resilient economies transmit more shocks to, and receive less spillovers from their peers. This finding is similar to Yépez (2020), who concluded that risk sharing is worse in emerging economies than in advanced economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emenike (2018) further demonstrated that the existence of bidirectional shock and volatility spillover between the Nigerian naira and CFA franc indicates an element of financial integration in West Africa. Senga and Cassimon (2019) documented, amongst others, the existence of significant integration among sub‐Saharan African bonds, and that less resilient economies transmit more shocks to, and receive less spillovers from their peers. This finding is similar to Yépez (2020), who concluded that risk sharing is worse in emerging economies than in advanced economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research is also motivated by the fact that, the extant financial development literature has not directly or indirectly focused on the positioning of this research(Gevorkyan & Kvangraven, 2016;Danquah, Quartey & Iddrisu, 2017;Asongu, Nwachukwu & Tchamyou, 2017;Kusi, Agbloyor, Ansah-Adu & Gyeke-Dako, 2017;Boamah, 2017;Amponsah, 2017;Kusi & Opoku-Mensah, 2018;Boateng, Asongu, Akamavi & Tchamyou, 2018;Bayraktar & Fofack, 2018;Asongu, Batuo, Nwachukwu & Tchamyou, 2018a;Senga, Cassimon & Essers, 2018;Gyeke-Dako, Agbloyor, Turkson & Baffour, 2018;Asongu, Raheem & Tchamyou, 2018b;Bokpin, Ackah & Kunawotor, 2018;Senga & Cassimon, 2019;Dafe, Essers & Volz, 2018).…”
mentioning
confidence: 99%
“…The Eurobond scandal in 2014 is another case of mega corruption, which raised questions about the use of proceeds from the international bond issuance and potential mismanagement of funds. The Kenyan government issued its first sovereign bond, raising $2.75 billion (Senga & Cassimon, 2020). While intended for infrastructure development and budgetary support, a significant portion of the proceeds went unaccounted for.…”
Section: Corruption Scandals In Kenyamentioning
confidence: 99%